Matrix methods in horadam sequences (2012)
Given the generalized Fibonacci sequence {Wn(a, b; p, q)} we can naturally associate a matrix of order 2, denoted by W(p, q), whose coefficients are integer numbers. In this paper, using this matrix, we find some identities and the Binet formula for the generalized Fibonacci–Lucas numbers.